Implementación de una estación meteorológica para el monitoreo atmosférico en el cantón La Maná. - Arteaga Bajaña, Edison Ariel (2022)
This project focuses on the installation of a meteorological station that allows obtaining climatological data in La Maná canton, and these can be used in future research work or in different applications where they are required, in addition, these data will be stored and monitored in real-time and for which will be used applications of web pages that already exist in the cloud and therefore the storage part will be done in the cloud allowing to build a history with this information. For this work, we used a LOGIA weather station with Wi-Fi which allows sending and receiving data relating to weather, the variables were: rainfall, temperature, solar radiation, relative humidity, and wind speed, The installation of the station will do at the Technical University of Cotopaxi extension La Mana in Block B.